Pengaruh Risiko Investasi Terhadap Return Saham Pada Perusahaan Otomotif Yang Terdaftar Di Bei Tahun 2011-2015 - Purba, Martha Cesaria; , Dra. Wuryaningsih DL, MM (2017)
This study aims to determine the effect of investment risk on stock returns in automotive companies listed on the Stock Exchange in 2011-2015. The data used is secondary data obtained through the annual financial statements published by the BEI. The technique used for sampling is purposive sampling. The sample in this study is the automotive company listed on the Stock Exchange 2011-2015 period. The number of samples taken 30 samples. The statistical analysis used in this study is multiple regression analysiss using SPSS. This study shows that the investment risk variables consisting of expected return, market risk or beta, business risk, financial risk significant effect on stock returns in automotive companies listed on the Stock Exchange in 2011-2015. The results showed 78,6 percent of the stock on automotive companies affected by variations four independent variables were used that expected return, market risk or beta, business risk, financial risk, while the remaining 21,4 percent is influenced by other variables beyond the study models.